Determinant Analysis of Tebing Tinggi Low Public Interest on Using Electronic Money - Collyn, Daniel; Zalukhu, Rika Surianto (Budapest International Research and Critics University, 2021)
The purpose of this research was to examine the effect of product quality, ease of use and risk on Tebing Tinggi low public interest on using electronic money in transactions. The dependent variable of the study is interest, while the independent variables are product quality, ease of use and risk. This research was conducted on residents of Tebing Tinggi City. The research population is 162,581 people. While the research sample amounted to 399 people. Determination of the number of samples using the slovin formula. The sampling technique used was simple random sampling technique. The type of data used is primary data. Data collection was done by using a questionnaire. Methods of data analysis using multiple linear regression analysis method. The results of the analysis show that product quality and ease of use partially have a positive and significant effect on Tebing Tinggi low public interest on using electronic money in transactions. Meanwhile, risk partially has a negative and significant effect on the interest of Tebing Tinggi low public interest on using electronic money in transactions